Bringing New Meaning to the Term “Adaptive Trial”: Challenges of Conducting Clinical Research During the Coronavirus Disease 2019 Pandemic and Implications for Implementation Science - Branch-Elliman, Westyn (Open Forum Infect Dis, 2020)
Although implementation of evidence-based practices takes an average of 17 years, in the context of the global pandemic, coronavirus disease 2019 (COVID-19) interventions were adopted in a greatly compressed time frame. This rapid uptake creates major challenges for conducting COVID-19 clinical research studies, because quickly evolving standards make it difficult to adapt in real time. The rapid dissemination and implementation of COVID-19 interventions is the realization of goals long pursued by the implementation science community. However, the downside of the rapid implementation is that low-quality evidence with little to no scientific vetting may be quickly integrated into clinical care, resulting in lost opportunities to advance our scientific understanding about how to manage infected patients. In the future, novel adaptive designs embedded into electronic health records (Embedded Quantified, Integrated-into-Practice Trial [EQuIPT] designs) that allow for easier and better access to clinical trials may simultaneously improve care and advance healthcare innovations.